2018
DOI: 10.1088/1674-1056/27/3/038103
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conduction of one-dimensional carbon nanomaterials and nanoarchitectures

Abstract: This review summarizes the current studies of the thermal transport properties of one-dimensional (1D) carbon nanomaterials and nanoarchitectures. Considering different hybridization states of carbon, emphases are laid on a variety of 1D carbon nanomaterials, such as diamond nanothreads, penta-graphene nanotubes, supernanotubes, and carbyne. Based on experimental measurements and simulation/calculation results, we discussed the dependence of the thermal conductivity of these 1D carbon nanomaterials on a wide r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 172 publications
(246 reference statements)
0
17
0
Order By: Relevance
“…It was shown that the thermal conductivity decreases with strain and increases almost linearly with a growing chain length ( Figure 6) [10]. A review of Zhan and Gu [23] gives a perspective of earlier works on thermal conduction of sp nhybridized variants of carbon. As it was established by molecular dynamics studies, κ grows from ∼200 W/mK to 680 W/mK when the chain length extends from 20 to 40 nm.…”
Section: Thermal Conductivitymentioning
confidence: 97%
See 1 more Smart Citation
“…It was shown that the thermal conductivity decreases with strain and increases almost linearly with a growing chain length ( Figure 6) [10]. A review of Zhan and Gu [23] gives a perspective of earlier works on thermal conduction of sp nhybridized variants of carbon. As it was established by molecular dynamics studies, κ grows from ∼200 W/mK to 680 W/mK when the chain length extends from 20 to 40 nm.…”
Section: Thermal Conductivitymentioning
confidence: 97%
“…A review of Zhan and Gu [23] gives a perspective of earlier works on thermal conduction of sp n -hybridized variants of carbon. As it was established by molecular dynamics studies, κ grows from ∼200 W/mK to 680 W/mK when the chain length extends from 20 to 40 nm.…”
Section: Electronic Properties Raman Response and Superconductivitymentioning
confidence: 99%
“…To date, only one study has investigated the thermal transport in CNT pillared graphene, [127] which however only measured the thermal resistance (9 × 10 −10 m 2 K W −1 ) at the CNT-graphene junction and demonstrated the high heat dissipation capability of the structure. In comparison, several papers have investigated the thermal conductivity (either in-plane or cross-plane) of the pillared graphene through molecular dynamics (MD) simulations, [128] from which the major factors influencing their thermal transport properties have been identified, such as the junction configurations, [129] and the CNT length and density (or inter-CNT distance). [130] Apart from the hybrid structures of the CNT-pillared graphene, there are also some other 3D carbon-based hierarchical structures being reported, as listed in Table 1, including the CNT/graphene oxide (GO) hierarchical structure, CNT/graphene hierarchical structure (annealed from CNT/GO at 1000 °C); [134] the 3D CNT network; [135] the CNT/ultrathin graphite foams; [136] and the 3D CNT intercalated graphite.…”
Section: Pillared Structuresmentioning
confidence: 99%
“…To date, only one study has investigated the thermal transport in CNT pillared graphene, which however only measured the thermal resistance (9 × 10 −10 m 2 K W −1 ) at the CNT–graphene junction and demonstrated the high heat dissipation capability of the structure. In comparison, several papers have investigated the thermal conductivity (either in‐plane or cross‐plane) of the pillared graphene through molecular dynamics (MD) simulations, from which the major factors influencing their thermal transport properties have been identified, such as the junction configurations, and the CNT length and density (or inter‐CNT distance) …”
Section: D Nanostructures For High Thermal Conductivitymentioning
confidence: 99%
“…Preliminary studies have shown that nanothreads have excellent mechanical properties comparable with those of CNT, for example, a high stiffness of 850 GPa and a bending rigidity of~5.35 × 10 −28 N•m 2 27,28 , and a structural-dependent ductility 29 . The carbon nanothread is also reported to possess a tailorable thermal conductivity 30,31 . Particularly, researchers have already reported the synthesis of single-crystalline packing of nanothreads (across hundreds of microns) 32 .…”
mentioning
confidence: 99%